Produção e uso do espaço público em Arapiraca, Alagoas: uma avaliação pós-ocupação do Parque Municipal Ceci Cunha e do Bosque das Arapiracas - Gomes Júnior, José de Souza (2016)
Public spaces are of great importance for the constitution of the city in many ways, including street beautification, the positive effects for the urban environment like breaking the monotony of the landscape, visual enhancement, etc., and the population like improving quality of life. The production of public space is directly linked to its manner of use by users, so it is essential to understand how they use and behaves in such spaces to enhance the projects of the same. The Post Occupancy Evaluation (POE) has been used in several studies and research as a method centered on user needs to improve the design process in order to identify the strengths and weaknesses of the environment under study to set recommendations, guidelines or proposals projects. In this research, the POE was used to analyze as it has the production and use of public spaces in the city of Arapiraca, Alagoas based the period 2000-2015, during which the city started to invest in the idea of "Metropolis of the Future" based on some socio-economic indicators. Were chosen two cases of built public spaces in this period and used different methods to raise both physical characteristics of the studied environments, as for measures of behavior and user satisfaction. As result of the research, is expected to understand how has given the production and use of public spaces in Arapiraca, seeking to list the positive and negative factors that help in obtaining guidelines for the improvement of these spaces and similar ones.